Selection of effective training categories
This study contains important information for designing conditioning programs on the basis of the energy use for various swimming events. The different energy categories are explained. 1. The best training paces will be those that are appropriate for the individual. It is unacceptable to set one speed for the whole squad. 2. Swimmers have to be tested and then made aware of the appropriate paces to be achieved in all categories of training work. When that is accomplished, training effects are more likely to be achieved. 3. Training in short-course pools for long-course events requires marked changes in training distances and performance paces. In the world of elite swimming, short- and long-course swimming are essentially two sports, their demands and training experiences being markedly different. To adjust short-course training for long-course competitions, training distances have to be increased by at least 15% (use the most convenient distance approximation), and speed increased by 7-9%. 4. Lactate testing is only useful for comparing responses to a known task. For example, if a repeated distance is completed at a lower lactate level, a better performance has occurred. How it is better will not be known. That must be determined from other measures and performance analyses. 5. Records of swimming sets and performances must be kept for analysis purposes. When that is done, it will be possible to relate improvements and declines to particular training experiences. 6. Categorizing workloads will facilitate better training plans. Author proposes a sequence of desirable training stages for endurance development with this writer's suggestions for categories and percentage of workload allocations.